QUALITY MANAGEMENT SYSTEM AND OPERATIONAL AGILITY OF FOOD AND BEVERAGES FIRMS IN RIVERS STATE, NIGERIA - OFOEGBU, Wilson Chukwuemeka; Laguo Livingstone Gilbert (Scholar Express Journals, 2021)
This study investigated the connection between quality management system and operational agility of food and beverages firms in Rivers State. The crosssectional study was performed with a populace size of 126 managers and supervisors of food and beverages firms. The data collected through questionnaire were analyzed using Spearman's Rank Coefficient to find out the connection between the components of quality management system and that of operational agility. The results showed that there is significant and positive connection between the proxies of quality management system and that of operational agility which revealed that quality management system as far as ceaseless improvement and focus on customer in the food and beverages firms’ agility functionality is enhanced. It was suggested that food and beverages firms should endeavour to continuously improve its product and services in order to develop agility that would help them adapt to changes in business environment.
Keywords: Quality Improvement; Customer Focus; Agile Development